Detailed phenotype of RNF213 p.R4810K variant identified by the Chinese patients with acute ischaemic stroke or transient ischaemic attack - Yuehua Pu; Yongjun Wang; Wei Li; Jing Jing; Hao Li; Zhe Xu; Xia Meng; Anxin Wang; Qin Xu; Yingting Zuo; Yue Suo; Hongyu Zhou (Stroke and Vascular Neurology)
Background and purpose The ring finger protein 213 gene (RNF213) p.R4810K variant increased the risk of acute ischaemic stroke (AIS) attributable to intracranial arterial stenosis (ICAS) in the Japanese and Korean populations. In this study, we aimed to examine the prevalence of the RNF213 p.R4810K variant in Chinese patients with AIS or transient ischaemic attack and identify the phenotype of the carriers.Methods We analysed data from the Third China National Stroke Registry. All included participants were divided into two groups by carrier status of the p.R4810K variant. The aetiological classification was conducted according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. The presence of ICAS and extracranial arterial stenosis (ECAS) was defined as 50%–99% stenosis or occlusion of any intracranial and extracranial artery. Logistic regression models and Cox regression models were used to evaluate the association of the p.R4810K variant with TOAST classification, stenosis phenotypes and clinical outcomes.Results A total of 10 381 patients were enrolled, among which 56 (0.5%) had the heterozygote GA genotype for p.R4810K. The variant carriers were younger (p=0.01), and more likely to suffer from peripheral vascular disease (p=0.04). The p.R4810K variant was associated with large-artery atherosclerosis (LAA) (adjusted OR=1.94, 95% CI 1.13 to 3.33), anterior circulation stenosis (adjusted OR=2.12, 95% CI 1.23 to 3.65) and ECAS (adjusted OR=2.29, 95% CI 1.16 to 4.51). Nevertheless, the p.R4810K variant was not associated with recurrence, poor functional outcome and mortality at 3 months and 1 year.Conclusions The RNF213 p.R4810K variant was associated with LAA, anterior circulation stenosis and ECAS in Chinese patients. Given the low carrying rate and only 1-year follow-up information, caution should be taken to interpret our findings in no statistically significant association between the p.R4810K variant and stroke prognosis in Chinese patients.